Demonstration‐scale enzymatic saccharification of sulfite‐pulped spruce with addition of hydrogen peroxide for LPMO activation. (25th April 2020) - Costa, Thales H. F.; Kadic', Adnan; Chylenski, Piotr; Várnai, Anikó; Bengtsson, Oskar; Lidén, Gunnar; Eijsink, Vincent G.H.; Horn, Svein Jarle
Abstract: The saccharification of lignocellulosic materials like Norway spruce is challenging due to the recalcitrant nature of the biomass, and it requires optimized and efficient pretreatment and enzymatic hydrolysis processes to make it industrially feasible. In this study, we report successful enzymatic saccharification of sulfite‐pulped spruce (Borregaard's BALI™ process) at demonstration scale, achieved through the controlled delivery of hydrogen peroxide (H2 O2 ) for the activation of lytic polysaccharide monooxygenases (LPMOs) present in the cellulolytic enzyme preparation. We achieved 85% saccharification yield in 4 days using industrially relevant conditions – that is, an enzyme dose of 4% (w/w dry matter of substrate) of the commercial cellulase cocktail Cellic CTec3 and a substrate loading of 12% (w/w). Addition of H2 O2 and the resulting controlled and high LPMO activity had a positive effect on the rate of saccharification and the final sugar titer. Clearly, the high LPMO activity was dependent on feeding the reactors with the LPMO co‐substrate H2 O2, as in situ generation of H2 O2 from molecular oxygen was limited. These demonstration‐scale experiments provide a solid basis for the use of H2 O2 to improve enzymatic saccharification of lignocellulosic biomass at large industrial scale.© 2020 The Authors. Biofuels, Bioproducts, and Biorefining published by Society of Chemical Industry and John Wiley & Sons, Ltd.